2003
DOI: 10.1016/s0301-2115(03)00290-2
|View full text |Cite
|
Sign up to set email alerts
|

Preconception nutritional intake and lifestyle factors: first results of an explorative study

Abstract: Objective: To describe nutritional intake and lifestyle factors in women planning pregnancy. Study design: A semi-quantitative, 1-month food frequency questionnaire and a questionnaire on health practices and personal views were filled out at home and verified by telephone interview. Results: One hundred and one women agreed to participate and data of 69 women were eligible for evaluation. Women planning pregnancy (n ¼ 46) consumed significantly more saturated fats and proteins, less carbohydrates and higher m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 11 publications
(13 reference statements)
1
33
0
3
Order By: Relevance
“…Of the three studies reporting dietary intake as nutrients, the consumption of folate (Hure et al, ; Pinto et al, ) and vitamin E (Hure et al, ; Pinto et al, ) was most frequently reported as being inadequate in the diets of preconceptual women. On the other hand, protein intake was more likely to exceed daily recommendations (de Weerd et al, ; Olmedo‐Requena et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the three studies reporting dietary intake as nutrients, the consumption of folate (Hure et al, ; Pinto et al, ) and vitamin E (Hure et al, ; Pinto et al, ) was most frequently reported as being inadequate in the diets of preconceptual women. On the other hand, protein intake was more likely to exceed daily recommendations (de Weerd et al, ; Olmedo‐Requena et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The included studies comprised 15 cross-sectional and three casecontrol studies. These studies were conducted in Australia (n = 4) (Bookari, Yeatman, & Williamson, 2017;Hure, Young, Smith, & Collins, 2009;Malek, Umberger, Makrides, & Zhou, 2016;Mishra, Schoenaker, Mihrshahi, & Dobson, 2015), China (n = 4) (Gao et al, 2013;Liu et al, 2015;Yang et al, 2017;Zhang, Zhou, Perkins, Wang, & Sun, 2017), India (n = 3) (Dahiya, 2002;Jood, Bishnoi, & Khetarpaul, 2002;Panwar & Punia, 1998), Pakistan (n = 1) (Sajjad & Khan, 2012), Poland (n = 1) (Bojar, Wdowiak, Humeniuk, & Blaziak, 2006), Canada (n = 1) (Pick, Edwards, Moreau, & Ryan, 2005), Spain (n = 1) (Olmedo-Requena et al, 2017), Japan (n = 1) (Okubo et al, 2011), Portugal (n = 1) (Pinto, Barros, & Santos Silva, 2009), and the Netherlands (n = 1) (de Weerd et al, 2003). Seventeen studies reported the dietary intake of pregnant women, and five reported the dietary intake of women in the preconception period.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Barriers for healthcare professionals are time constraints, limited expertise and interest and the lack of reimbursement of healthcare costs. However, it seems promising, based on our own experience and that of others, that individuals are much more likely to be motivated to modify their lifestyle during the preconception and pregnancy life course because of the short-term benefits of having a healthy baby (de Weerd et al 2003;Inskip et al 2009;Hammiche et al 2011). Therefore, the preconception and pregnancy window should be considered as the earliest and unique period in the life course during which individuals may be most likely to change their lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the literature primarily assesses pregnancy intentions retrospectively, potentially introducing bias [17]. The few studies measuring pregnancy intentions prospectively typically report no relationship between pregnancy intentions and smoking, alcohol, physical activity, or diet [18][19][20][21][22][23] and none measured psychological factors. Furthermore, only one study has been conducted outside the U.S. [23].…”
Section: Introductionmentioning
confidence: 99%